Addictions in patients with atopic dermatitis: a cross‐sectional pilot study in Germany. (8th October 2021) - Pilz, A.C.; Durner, V.; Schielein, M.C.; Schuster, B.; Beckmann, J.; Biedermann, T.; Eyerich, K.; Zink, A.
Abstract: Background: Atopic dermatitis (AD) is the most common chronic inflammatory skin disease worldwide and displays many atopic, but also non‐atopic comorbidities. Among the latter, mental health disorders such as depression have been extensively studied. However, data on addictions are still rare. Objectives: The aim of this study was to assess the prevalence of different kinds of addictions in adult AD patients using a single‐centre approach. Methods: This non‐interventional cross‐sectional study was performed from 03/2020 to 05/2020 at the Department of Dermatology of a large German university hospital. Participants with a diagnosis of AD confirmed by a dermatologist answered questions about disease severity (patient‐oriented eczema measure, POEM), quality of life (Dermatology Life Quality Index, DLQI) and smoking habits. They were screened for problematic alcohol consumption, drug abuse, internet addiction and pathological gambling using internationally established and validated questionnaires. Results: 157 patients (56.1% female; mean age of 49.9 ± 20.4) with an average POEM of 13.7 ± 7.5 and DLQI of 6.1 ± 5.4 were evaluated. 14.1% were identified as regular smokers, 12.1% screened positive for alcohol dependency, 6.4% for drug use disorders, 4.5% for Internet addiction and 3.2% for pathological gambling. Co‐occurrences of different addictions were observed, and a positive correlation was noted between DLQI scores and smoking. Conclusions: In summary, this study hints at elevated positive screening rates for problematic alcohol consumption, drug use disorders, Internet addiction and problem gambling compared with the general population. Screening routinely for addictions may improve patient‐centred health care of AD patients.